Penerapan Project-Based Learning (PjBL) untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Yusni Yusni; Yogi Setiadi Saputra; Marlina Bakri; Nurrahmayani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Students' critical thinking skills are still relatively low, mainly due to the learning process being dominated by conventional approaches, centered on lecturers, and emphasizing memorization. This condition has the potential to hinder students' readiness to face the academic and workplace demands of the 21st century. One learning model that is considered capable of addressing this problem is Project-Based Learning (PjBL). This study aims to analyze the improvement of students' critical thinking skills through the application of Project-Based Learning (PjBL) in Indonesian Language courses. The study used a quantitative method with a quasi-experimental design in the form of a pretest-posttest. The study sample consisted of 38 sixth-semester Midwifery Study Program students at Mega Buana University, Palopo, selected using a purposive sampling technique. Data were collected through critical thinking skills tests, observations, questionnaires, interviews, and documentation. Quantitative data analysis was conducted by comparing pretest and posttest scores, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed an increase in the average critical thinking skills score from 65.24 to 82.37, an increase of 17.13 points. After implementing PjBL, students were predominantly in the good and excellent categories. These findings indicate that PjBL is effective in improving students' critical thinking skills through active engagement in investigation, problem-solving, collaboration, and project development.